William Shatner : you can call me Bill [videorecording (DVD)] - Shatner, William (Decal, 2024)
An intimate portrait of William Shatner's personal journey across nine decades of a boldly lived and fully realized life, YOU CAN CALL ME BILL strips away all the masks he has worn during his storied career, to reveal the man behind it all.